AI‐Involved Inventions and Patentability: Emotional Perception AI v Comptroller‐General of Patents, Designs and Trade Marks. - Arıkan, Özgür (Modern Law Review, 2025)
The growing use of artificial intelligence technologies in inventions has significantly increased the number of AI‐involved patent applications. This trend has prompted a reassessment of the boundaries defining excluded subject matter in patent law, as exemplified in Emotional Perception AI v Comptroller‐General of Patents, Designs and Trade Marks. While computer programs are traditionally classified as excluded subject matter and as such ineligible for patent protection, exceptions apply to computer‐implemented inventions that demonstrate a technical contribution beyond the ordinary functioning of a computer. The question addressed in Emotional Perception AI v Comptroller‐General of Patents, Designs and Trade Marks was whether inventions involving artificial intelligence, particularly artificial neural networks, should be treated the same as conventional computer‐implemented inventions regarding patentability under section 1(2) of the Patents Act 1977. Although the High Court adopted a pioneering approach to this issue, the Court of Appeal rejected this approach, and instead adhered to the conventional perspective on computer‐implemented inventions.